Effect of low tidal volume ventilation on lung function and inflammation in mice - Goldmann Torsten; Karp Dörte; Hauber Hans P; Vollmer Ekkehard; Zabel Peter (BMC Pulmonary Medicine, 2010)
Abstract Background A large number of studies have investigated the effects of high tidal volume ventilation in mouse models. In contrast data on very short term effects of low tidal volume ventilation are sparse. Therefore we investigated the functional and structural effects of low tidal volume ventilation in mice. Methods 38 Male C57/Bl6 mice were ventilated with different tidal volumes (Vt 5, 7, and 10 ml/kg) without or with application of PEEP (2 cm H2O). Four spontaneously breathing animals served as controls. Oxygen saturation and pulse rate were monitored. Lung function was measured every 5 min for at least 30 min. Afterwards lungs were removed and histological sections were stained for measurement of infiltration with polymorphonuclear leukocytes (PMN). Moreover, mRNA expression of macrophage inflammatory protein (MIP)-2 and tumor necrosis factor (TNF)α in the lungs was quantified using real time PCR. Results Oxygen saturation did not change significantly over time of ventilation in all groups (P > 0.05). Pulse rate dropped in all groups without PEEP during mechanical ventilation. In contrast, in the groups with PEEP pulse rate increased over time. These effects were not statistically significant (P > 0.05). Tissue damping (G) and tissue elastance (H) were significantly increased in all groups after 30 min of ventilation (P < 0.05). Only the group with a Vt of 10 ml/kg and PEEP did not show a significant increase in H (P > 0.05). Mechanical ventilation significantly increased infiltration of the lungs with PMN (P < 0.05). Expression of MIP-2 was significantly induced by mechanical ventilation in all groups (P < 0.05). MIP-2 mRNA expression was lowest in the group with a Vt of 10 ml/kg + PEEP. Conclusions Our data show that very short term mechanical ventilation with lower tidal volumes than 10 ml/kg did not reduce inflammation additionally. Formation of atelectasis and inadequate oxygenation with very low tidal volumes may be important factors. Application of PEEP attenuated inflammation.